Child with hepatic hydatid cyst: A diagnostic uncertainty - Ranjani, Shashi; Mehdi, Intezar; Mahadevappa, Basant; Swamy, Shivakumar (Indian Journal of Child Health, 2019)
Many parts of India are endemic for hydatid cyst, and hence, the most common diagnosis of a hepatic cyst in such regions is hydatid cyst. Undifferentiated embryonal sarcoma of the liver (UESL) is a rare differential diagnosis for hepatic hydatid cyst as the clinical and radiological features of hydatid cysts and UESL overlap. Here, we report a 4-year-old boy with hepatic cyst, who was initially diagnosed as hepatic hydatid cyst, which was later confirmed as UESL. The child was successfully treated with chemotherapy. This case report highlights the need to spread awareness about UESL, as prompt diagnosis and treatment improves prognosis of the same.